Service quality of Maybank towards their customers - Khairuddin, Solahuddin (2001)
Customer satisfaction and promotions are related regarding the service quality of a service provider. In the banking industry, service quality is important in order to retain their customer and attract new ones. Using the banking industry as the setting, the researcher evaluates the satisfaction of customers towards the service offered and also the promotional efforts from the client perspectives. The findings suggest that greater promotional efforts can attract people and retain existing customers and the relationship between customer satisfaction and the services offered. The implications of the research and suggestions are discussed.